2013
DOI: 10.1634/theoncologist.2012-0404
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Capecitabine, Oxaliplatin, and Bevacizumab in the Treatment of Metastatic Esophagogastric Adenocarcinomas

Abstract: Background. Esophageal and gastric cancers often present at an advanced stage. Systemic chemotherapy is the mainstay of treatment, but survival with current regimens remains poor. We evaluated the safety, tolerability, and efficacy of the combination capecitabine, oxaliplatin, and bevacizumab in the treatment of metastatic esophagogastric adenocarcinomas.Methods. Thirty-seven patients with metastatic or unresectable gastric/gastroesophageal junction tumors were enrolled and treated with capecitabine 850 mg/m 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 15 publications
1
28
1
Order By: Relevance
“…44 Yet, another biomarker that was shown to be inversely correlated with PFS after treatment with bevacizumab, oxaliplatin and capecitabine regimen is neoropilin-2 (NRP-2). 45 Patients with metastatic/unresectable gastroesophageal junction tumors having greater NRP-2 expression had shorter PFS, suggesting the role of NRP-2 in anti-VEGF therapy. 45 Thus, multiple angiogenic biomarkers have prognostic and predictive importance for mCRC patients receiving bevacizumab plus XELOX combination therapy.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…44 Yet, another biomarker that was shown to be inversely correlated with PFS after treatment with bevacizumab, oxaliplatin and capecitabine regimen is neoropilin-2 (NRP-2). 45 Patients with metastatic/unresectable gastroesophageal junction tumors having greater NRP-2 expression had shorter PFS, suggesting the role of NRP-2 in anti-VEGF therapy. 45 Thus, multiple angiogenic biomarkers have prognostic and predictive importance for mCRC patients receiving bevacizumab plus XELOX combination therapy.…”
Section: Discussionmentioning
confidence: 96%
“…45 Patients with metastatic/unresectable gastroesophageal junction tumors having greater NRP-2 expression had shorter PFS, suggesting the role of NRP-2 in anti-VEGF therapy. 45 Thus, multiple angiogenic biomarkers have prognostic and predictive importance for mCRC patients receiving bevacizumab plus XELOX combination therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, high levels of plasma VEGF-A predicted an improvement in OS (HR = 0.72; 95% CI, 0.57 to 0.93), and low expression of tumor neuropilin-1 also predicted an improvement in OS (HR = 0.75; 95% CI, 0.59 to 0.97) in the bevacizumab group. In contrast, the predictive value of neuropilin-1 was not noted in another phase II trial (36). According to an analysis of AVAGAST subgroups, VEGF-A and neuropilin-1 had the ability to predict OS only in non-Asian patients (37).…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 91%
“…The disease control rate (DCR) was 79 % with 6.6 months of PFS and 11.1 months of OS. Finally, Uronis et al [39] investigated the combination of bevacizumab with capecitabine and oxaliplatin in primary metastatic esophagogastric adenocarcinomas (RR 51 %, PFS 7.2 months, OS 10.8 months).…”
Section: Bevacizumabmentioning
confidence: 99%
“…For both biomarkers, subgroup analyses demonstrated significance only in patients from non-Asian regions. Finally, an exploratory analysis of a phase II trial of bevacizumab in combination with capecitabine and oxaliplatin showed that tumor expression of NRP-1 and NRP-2 was assessed and correlated with outcome [39]. However, the small sample size and the absence of a control group do not allow for any conclusions to be drawn regarding the predictive effect of these biomarkers.…”
Section: Biomarkersmentioning
confidence: 99%